Spatial vitality variation in community parks and their influencing factors - Jingjing Zhang; Xiao Hu; Juan Wang (PLoS ONE, 2025)
Community parks are the primary locations for urban residents to engage in nature, exercise, and establish social contact. This study used System for Observing Play and Recreation in Communities (SOPARC) to conduct field surveys of three typical community parks in Hangzhou, focusing on analyzing the differences in subspace vitality within community parks. First, we classified park spaces into four types: courts, lawns, fitness grounds, and pavilions. We selected 11 variables to assess the landscape features of the subspaces; then, visitor density, activity richness, activity evenness, and time stability were selected to quantify the vitality characteristics of the four space types. Finally, a mixed linear model was used to explore the relationship between landscape features and different types of spatial vitality and to select the key influencing factors affecting spatial vitality. The study found that (1) the vitality of different types of spaces in community parks differed significantly, showing three types of vitality. Among them, high activity richness and evenness, low visitor density and time stability were observed in courts and lawns. However, fitness grounds showed the opposite vitality pattern. Pavilions exhibited exceptionally high visitor density but low activity richness, activity evenness, and time stability. (2) The key influences affecting subspace vitality mainly include hydrophilicity and accessibility and exhibit enhancing or inhibiting effects on different types of spaces. The study found water-friendliness positively contributed to visitor density, activity richness, and time stability in all types of subspaces. Sports facilities increased visitor density and time stability on courts, lawns, and fitness grounds but reduced their activity evenness. Accessibility had an enhancing effect on activity richness but an inhibiting effect on the activity evenness of pavilions. We suggest that community parks be made more vibrant by adding natural elements to the space, installing multifunctional and compact facilities, and subdividing spatial functions.